Dynamics of vegetation and its responses to terrain factors with Mann-Kendall approach: a case study in Tiaoxi watershed, Taihu Lake - JIANG Zhen-lan; JING Chang-wei; LI Dan; YU Xiang; WU Jia-ping (浙江大学学报. 农业与生命科学版, 2011)
Mann-Kendall approach was applied for characterizing the features and mechanisms of vegetation changes with time, elevation and slope in the Tiaoxi watershed, Taihu Lake region, Zhejiang Province, east China. The results indicated that the annual vegetation in the area fluctuated dramatically and showed a moderate trend of increase from 2000 to 2010, but in 2004, the coverage dropped to the lowest level; The variability of spatial distribution also showed a moderate trend of increase during the study period, with the spatial heterogeneity reaching the highest between 2002 and 2004; the vegetation coverage kept increasing while the spatial heterogeneity decreased with the increment of elevation and slope. At elevation of about 200 m or slope around 15 degrees, there were signs of catastrophe change. The results above reveal the trend of vegetation changes with time, elevation and slope, and identify when and where the catastrophes occur, which lays a sound basis for further study on the spatiotemporal dynamics of vegetation and its driving factors.